Unpacking The Concept Of Nationalism Within Russian Eurasianism - Torosyan, Veronika (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Eurasianism was first developed in the first half of the 20th century among Russian emigrants. It advocated a typology of human civilizations based on cultural uniqueness and claimed the equal importance of all cultures. The issue of nationalism was connected with the understanding of culture in the writings of the Eurasianists. They believed that all the peoples of the former Russian Empire should live together in the same State for ecological and cultural reasons, thus forming a common civilization. This is how the territory of the state was formed (whether it was called the Russian Empire, the USSR or Eurasia), which under any conditions had to maintain its integrity. In the meantime, Eurasianism alternatively saw society as having a “personality” and required special descriptive terms such as “folk personality”, “symphonic personality,” “aggregate personality”, “cultural organism” etc. Thus, the purpose of the article is to analyze the understanding of the concept of nationalism in the works of Russian Eurasianists, based on the definition given by the theorist Anthony Smith as it is fully compatible to demonstrate changes in the understanding of nationalism in their works and to answer the question: how nationalism was defined precisely in Eurasianism? The paper argues that nationalism, as explained in Russian Eurasianism, which encompasses ethnic and civil aspects of the Smith definition and subsequently evolved into the idea of a common civilization, has the potential for being used in multi-ethnic and multicultural society as a unifying instrument.
Keywords: Պատմություն; Հասարակական-քաղաքական կյանք